Assessing the host status of banana and other plant species to the enset root mealybug Paraputo ensete (Williams & Matile-Ferrero) (Hem.: Pseudococcidae) in Ethiopia - Erenso, Fikadu; Blomme, Guy; Muanenda, Mitiku; Kearsley, Elizabeth; Goergen, Georg E.; Addis, Temesgen (Academic Journals, 2022)
Ninety backyard gardens in the south-eastern Ethiopian highlands with enset (Ensete ventricosum (Welw.) Cheesman), banana and various annual crops were assessed for the presence of enset root mealybugs (Paraputo ensete (Williams & Matile-Ferrero)). This study presents the first observation of enset root mealybugs on banana. This pest has until now been exclusively recorded on enset in Ethiopia. In the Dilla Zuria district of the Gedeo zone, southern Ethiopia, infested banana mats of the ‘Pisang Awak’ (ABB genome) landrace were observed adjacent to infested enset plants in three small-holder backyard gardens. As roots of banana mats and enset plants were overlapping and intertwined, and large numbers of mealybugs were observed on enset roots, possibly representing an overpopulation, the observed mealybugs on banana might have represented a “chance infestation". The smaller size of mealybugs on banana roots might indicate a non-optimal host status of this crop. Experimental choice and no-choice pot trials however provided another indication of the possible host potential of ‘Pisang Awak’ and of an additional banana cultivar ‘Matooke’ (AAA-East African Highland). The enset root mealybug was able to fully develop, produce viable offspring and survive on both banana cultivars. Not all investigated banana cultivars presented this host status, and the susceptibility of most Musa cultivars remains low.